The Modified Role of Strategic Reasoning in Enhancing the Influential Relationship between Strategic Leadership and Strategic Stretch: An Analytical Survey Study of the Opinions of a Sample of Administrative Leaders in Akre University of Applied Scienc - Bashqali, Mahmoud Mohammed Amin (The Arab Journal of Administration, 2025)
This research aims to explore the role of strategic reasoning in amplifying the relationship between strategic leadership and strategic stretch. The study adopted the inductive method (descriptive-analytical). In light of its objective, the problem was summarized by a set of questions, including: What is the extent of the study sample’s awareness of the dimensions of strategic leadership in the university under study? What are the indicators of strategic expansion and strategic reasoning for the university under study? Is there a significant correlation and impact between strategic leadership and strategic expansion in the university under study? And does strategic reasoning play a moderating role in the relationship between strategic leadership and strategic expansion in the university under study? Data was gathered via questionnaires distributed among a random sample of 65 administrative leaders within the university under study. A total of 51 completed questionnaires were collected, yielding a response rate of 78%. Statistical analysis was conducted using SPSS V. 22.The findings reveal a significant correlation between strategic leadership and strategic stretch within the sample. Moreover, strategic leadership significantly influences strategic stretch within the same sample, and strategic reasoning augments this influence. Several recommendations emerge from the study. Firstly, it is imperative for administrative leaders within the university to prioritize human capital development by implementing tailored training programs aimed at nurturing the skills of talented individuals in alignment with organizational needs. Secondly, fostering an environment conducive to innovation is essential for achieving strategic stretch. This involves establishing transparent evaluation criteria that recognize and reward creative initiatives from employees.